New Weighting Methods for Phylogenetic Tree Reconstruction Using Multiple Loci - Misawa, Kazuharu (Springer-Verlag, 2012)
Efficient determination of evolutionary distances is important for the correct reconstruction of phylogenetic trees. The performance of the pooled distance required for reconstructing a phylogenetic tree can be improved by applying large weights to appropriate distances for reconstructing phylogenetic trees and small weights to inappropriate distances. We developed two weighting methods, the modified Tajima–Takezaki method and the modified least-squares method, for reconstructing phylogenetic trees from multiple loci. By computer simulations, we found that both of the new methods were more efficient in reconstructing correct topologies than the no-weight method. Hence, we reconstructed hominoid phylogenetic trees from mitochondrial DNA using our new methods, and found that the levels of bootstrap support were significantly increased by the modified Tajima–Takezaki and by the modified least-squares method. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00239-012-9513-4) contains supplementary material, which is available to authorized users.